(X-3)(x-10)=120

Simple and best practice solution for (X-3)(x-10)=120 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-3)(x-10)=120 equation:



(X-3)(X-10)=120
We move all terms to the left:
(X-3)(X-10)-(120)=0
We multiply parentheses ..
(+X^2-10X-3X+30)-120=0
We get rid of parentheses
X^2-10X-3X+30-120=0
We add all the numbers together, and all the variables
X^2-13X-90=0
a = 1; b = -13; c = -90;
Δ = b2-4ac
Δ = -132-4·1·(-90)
Δ = 529
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{529}=23$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-13)-23}{2*1}=\frac{-10}{2} =-5 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-13)+23}{2*1}=\frac{36}{2} =18 $

See similar equations:

| 12(x-3)+18=-6x | | 14+9x=8(10+X) | | x^2-4x+11=2x+2 | | 8k-2(k+7)=-14+6k | | t*3-3=11 | | 13(y+3)=3y+39 | | a*6+5=1 | | 5(x-6)+3=7x-4 | | X^2-2x-3=x+1 | | p=-1=5p+3p-8 | | -5=b+(-5) | | 20x-9=12x-29 | | 6+5a=5a-3 | | 8(4w+5)/5=6 | | 22=r+2 | | p-14=-33 | | 4p+2=9p-18 | | 15x-39=14x-23 | | X+8+.5x=23 | | 20+k=2 | | 10=p/7 | | 3x^2+4x^2=15^2 | | 4*5x=54 | | -17=-12+n | | -19m=171 | | 8+7x-3=3x-7 | | 6x-7+5x+1=0 | | 4*x*5=54 | | -15z-12=2z+15 | | 4^-2n=16 | | 5x+8x-3=15x+17 | | -5+11g=19-13g |

Equations solver categories